Management of COVID-19-Positive Bangladeshi Patients at Home: A Telephone-based Pilot Study (Global Journal of Medical Research, 2023)
The recent COVID-19 pandemic highlighted the challenges in healthcare settings due to the scarcity of medical resources like hospital beds and healthcare professionals to manage critical cases. During this critical period, healthcare professionals emphasized on saving lifethreatening cases, including moderate to severe COVID-19 cases, as they might need either ventilators or treatment in intensive care units. As a result, the national and international health policymakers, including WHO, suggested managing the suspected or confirmed COVID-19 patients without symptoms or having mild symptoms at home to reduce the burden on hospitals and trained healthcare professionals. Hence, we aimed to conduct a telephone-based pilot study to examine the feasibility before conducting a large-scale study on home-care treatment and management of the confirmed or suspected COVID-19 Bangladeshi patients, either asymptomatic or mild-symptomatic, during the home quarantine period.
Keywords: COVID-19-positive; Bangladeshi patients; treatment and management; home-care